2015
DOI: 10.1159/000373889
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Relationship between Plasma Pentraxin 3 Levels and Gestational Diabetes Mellitus?

Abstract: Background: Pentraxin 3 (PTX3) is a novel vascular inflammatory marker which increases in vascular events such as diabetes mellitus. The aim of this study was to investigate the relationship between serum PTX3 levels and gestational diabetes mellitus (GDM). Methods: This prospective observational study was comprised of 88 pregnant women with singleton pregnancies. The subjects were classified into 3 groups according to their response to a 50-gram glucose challenge test (GCT) and a 100-gram oral glucose toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…PTX3 was negatively correlated with QUICKI, which showed that a higher level of PTX3 is related to lower insulin sensitivity, but more studies are needed to determine the mechanism. The present finding is in line with other recent studies (24,37). Publications in the literature have reported that potential predictors of GDM, when used alone for screening, have some shortcomings, such as a low detection rate and high false positive rate.…”
Section: Discussionsupporting
confidence: 92%
“…PTX3 was negatively correlated with QUICKI, which showed that a higher level of PTX3 is related to lower insulin sensitivity, but more studies are needed to determine the mechanism. The present finding is in line with other recent studies (24,37). Publications in the literature have reported that potential predictors of GDM, when used alone for screening, have some shortcomings, such as a low detection rate and high false positive rate.…”
Section: Discussionsupporting
confidence: 92%
“…The reason for this discrepancy is unclear, but could involve a lower number of patients with GDM and in particular of controls in the two other studies, and notably in one of the studies there was no differences in lipid values, BMI or measures of glucose metabolism between GDM and non-GDM women suggesting that they are studying a milder GDM phenotype, which is also supported by the GDM diagnostic criteria used (ADA and NDDG) [ 15 , 16 ]. Furthermore, while Yilidrim et al [ 16 ] observed a positive correlation between PTX3 levels and response to the glucose challenge test, we found positive correlations with β cell function and insulin sensitivity and a negative correlation with insulin resistance, suggesting a potential beneficial effect of PTX3. A protective role for PTX3 in normal pregnancy, with increased levels closer to gestation, as observed in our study, has been reported in several other publications [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 97%
“…Based on its relation to vascular inflammation, PTX3 has been suggested to be involved in vascular complication during pregnancy. Indeed, PTX3 levels are markedly elevated in women with preeclampsia [ 13 ] and type 1 diabetes during pregnancy [ 14 ], and have been shown to correlate with the degree of glucose intolerance in women with GDM [ 15 , 16 ]. However, PTX3 levels have not been prospectively evaluated during pregnancy and related to future CVD risk.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose and PTX3 might involve a mutual cause–effect relationship, and they create a vicious cycle by either induction or acceleration of vascular inflammation in patients with GDM. But, interestingly, there is also one study that reported the PTX3 concentration was lower in women with subsequent GDM than normal pregnancies, the limited cases of that study might be the reason for the discrepancy.…”
Section: Discussionmentioning
confidence: 97%